2016
DOI: 10.1038/srep26711
|View full text |Cite
|
Sign up to set email alerts
|

The Maternal Effect Genes UTX and JMJD3 Play Contrasting Roles in Mus musculus Preimplantation Embryo Development

Abstract: During the process of embryonic development in mammals, epigenetic modifications must be erased and reconstructed. In particular, the trimethylation of histone 3 lysine 27 (H3K27me3) is associated with gene-specific transcriptional repression and contributes to the maintenance of the pluripotent embryos. In this study, we determined that the global levels of the H3K27me3 marker were elevated in MII oocyte chromatin and decrease to minimal levels at the 8-cell and morula stages. When the blastocyst hatched, H3K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 57 publications
2
26
0
Order By: Relevance
“…Previous studies have shown that the knockdown of KDM6B or overexpression of KDM6A in MEFs results in significantly more iPSC colonies compared with wild-type cells [55,56]. Interestingly, the knockdown of KDM6B in SCNT embryos leads to a moderate increase in the expression of KDM6A, consistent with our previous findings in mouse parthenogenetic embryos [41]. While our paper was under preparation, another study reported the identification of H3K27me3-dependent imprinting genes (which include Gab1, Sfmbt2, and Slc38a4), and previous studies have shown that these genes exhibit a loss of imprinting in SCNT embryos [57,58].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Previous studies have shown that the knockdown of KDM6B or overexpression of KDM6A in MEFs results in significantly more iPSC colonies compared with wild-type cells [55,56]. Interestingly, the knockdown of KDM6B in SCNT embryos leads to a moderate increase in the expression of KDM6A, consistent with our previous findings in mouse parthenogenetic embryos [41]. While our paper was under preparation, another study reported the identification of H3K27me3-dependent imprinting genes (which include Gab1, Sfmbt2, and Slc38a4), and previous studies have shown that these genes exhibit a loss of imprinting in SCNT embryos [57,58].…”
Section: Discussionsupporting
confidence: 91%
“…As described above, the ectopic overexpression of KDM6A mRNA at low concentrations improved the SCNT efficiency. We have previously shown that mouse parthenogenetic embryos in which KDM6B is knocked down exhibited a moderate increase in KDM6A expression . We speculated that KDM6B knockdown could facilitate ZGA and improve SCNT efficiency.…”
Section: Resultsmentioning
confidence: 96%
“…Previous studies have shown that the knockdown of KDM6B or over-expression of KDM6A in MEFs results in significantly more iPSC colonies compared with wild-type cells [56, 57]. Interestingly, the knockdown of KDM6B in SCNT embryos leads to a moderate increase in the expression of KDM6A, consistent with our previous findings in mouse parthenogenetic embryos [42]. While our paper was under preparation, another study reported the identification of H3K27me3-dependent imprinting genes (which include Gab1, Sfmbt2 and Slc38a4) , and previous studies have shown that these genes exhibit a loss of imprinting in SCNT embryos [58, 59].…”
Section: Discussionsupporting
confidence: 91%
“…As described above, the ectopic overexpression of KDM6A mRNA at low concentrations improved the SCNT efficiency. We have previously shown that mouse parthenogenetic embryos in which KDM6B is knocked down exhibited a moderate increase in KDM6A expression [42]. We speculated that KDM6B knockdown could facilitate ZGA and improve SCNT efficiency.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation